How do Government Expenditures by Function Affect Economic Growth? Evidence from Indonesia - Panjaitan, Rido Parulian; Sukmono, Renny; Fuady, Muhammad Syahrul; Salsabila, Nurfiryal; Hadiantoro, Farhan (Universitas Muhammadiyah Ponorogo, 2026)
This study addresses a key gap in the empirical literature on fiscal policy and economic growth: while numerous studies assess the impact of total government spending, few examine the differential effects of expenditures by function under the COFOG framework, particularly in emerging economies such as Indonesia. Understanding these functional impacts is essential for aligning budget priorities with long-term development goals, especially amid fiscal volatility and shifting political agendas. Using annual realized expenditure data by function from the Ministry of Finance for 2005–2023, this study employs a multiple regression model grounded in the Keynesian Growth Model and Endogenous Growth Model to evaluate the impact of functional spending on long-term economic growth. The analysis spans four presidential terms (Susilo Bambang Yudhoyono 2004–2014; Joko Widodo 2014–2024) and encompasses major domestic and global economic shocks during the period. Findings shows that Economic Affairs and General Public Services have consistently received the largest shares of Indonesia’s budget from 2005–2023, while Health accounts for a relatively small portion. Compared to OECD countries, which prioritize Social Protection, Indonesia’s spending pattern emphasizes Economic Affairs and Education, with allocations fluctuating significantly from year to year. Regression results show that only Health expenditure has a positive and statistically significant effect on economic growth, aligning with the role of human capital in long-term productivity. In contrast, Social Protection shows a negative significant effect, while major categories such as Economic Affairs, Public Order and Safety, and Education have no significant impact. These findings underscore that the quality, efficiency, and strategic orientation of spending, rather than its size, are critical for aligning fiscal policy with sustainable growth objectives.